SYN-TECTONIC SEDIMENTATION ASSOCIATED WITH THREE-DIMENSIONAL FAULT-BEND FOLD STRUCTURES: A NUMERICAL APPROACH - Bernal A.; Hardy S. (My University, 2002)
Syn-tectonic sediments (growth strata) in compressional structures are three-dimensional (3D) features whose geometry reflects both the style of deformation and the distribution of accommodation space in the system. Previously, numerical modelling of growth strata in compressional settings has generally been done in two-dimensions in the plane of the transport direction. In contrast, in this paper we examine growth strata associated with a 3D fault-bend fold that exhibits variations in slip along-strike. A forward numerical modelling approach is used to investigate the 3D geometry of syn-tectonic sediments under a variety of conditions.We consider a fault-bend fold in which slip decreases linearly from the centre of the structure to zero displacement at the edges in a direction perpendicular to transport. We make use of kink-band kinematics to describe the growth of the structure. Two specific models are presented, which consider both (1) background (regional) sedimentation and (2) local erosion, transport and sedimentation. The first model approximates structures developed in submarine environments where structural growth may lead to the development of a bathymetric high. The model shows considerable lateral changes in the geometries of growth strata along the structure, with unconformities being limited to regions of high displacement, and with growth triangles being variably developed, but in some circumstances difficult to recognise. The subaerial model approximates structures developed in settings where sediments simply aggrade to the local base level. In this model, unconformities are much more prominent as growth sedimentation is often limited to regions of lower displacement.The results presented here emphasise the utility of using 3D information on stratigraphic architectures to decipher the growth style and deformational history of natural structures. In particular, we show that cross-sections oblique to the transport direction may contain complex and highly variable pre- and syn-tectonic geometries that reflect both kink-band migration and limb rotation. The use of oblique two-dimensional (2D) information to interpret 3D structures could produce misinterpretations if the complexities of stratigraphic configurations in three-dimensions are not taken into account.
Keywords: SYNTECTONIC SEDIMENTATION; THREE-DIMENSIONAL FAULT-BEND FOLD STRUCTURES; GROWTH STRATA